Research on Correlations of lncRNA ST7-AS1 with Progression and Therapeutic Targets of Esophageal Cancer - Xiao Lin; Sijia Sun; JiWen Zhang; Yan Cai; Quan Cheng (The Turkish Journal of Gastroenterology)
Background/Aims: Esophageal cancer is a highly prevalent gastrointestinal tumor in China, resulting in a significant number of deaths annually. In this paper, we investigated the regulatory role and therapeutic potential of aberrant ST7-AS1 expression in esophageal cancer.